y = -1 + 3/8x
2x - 5y = 6
Substitute the first equation into the second equation, since y is already by itself.
2x - 5(-1 + 3/8x) = 6
2x + 5 - 15/8x = 6
2x - 15/8x = 1
16/8x - 15/8x = 1
1/8x = 1 Multiply 8 on both sides to get x by itself
x = 8
Plug x into either of the equations.
y = -1 + 3/8(8)
y = -1 + 3
y = 2
2(8) - 5y = 6
16 - 5y = 6
-5y = -10
y = 2
(8,2)
Answer:
16 by 8
Step-by-step explanation:
Answer:
4(x-3)(x+6)
Step-by-step explanation:
We factor out the 4 first since all numbers are divisible by 4. That leaves us with x^2+3x-18.
Then we factor this to get (x-3)(x+6).
So the factored form of the equation is 4(x-3)(x+6)
Answer:
Step-by-step explanation:
x=14 is a vertical line with undefined slope
It has no y intercept and has only x intercept of 14.
Answer:
2
Step-by-step explanation:
12 x - 15 = 6x - 3
12 x - 6x = 15 - 3
6x = 12
x = 12/6 = 2